Antibodi Monoklonal Anti-CD3 Sebagai Terapi Diabetes Mellitus Tipe 1: Sebuah Kajian Sistematis dan Meta-analisis - Visakha Vidyadevi Wiguna; Abiyyu Didar Haq; Luh Ade Dita Rahayu (Faculty of Medicine Universitas Mataram, 2021)
Introduction: Type 1 Diabetes Mellitus (T1DM) is a chronic autoimmune disease which marked by a persistent increase in blood glucose (hyperglycemia). T1DM is thought to be caused by an autoreactivity of T cell which mediates the apoptosis of insulin-producing cells in the pancreas. Those mechanism causes a life-long dependance on exogen insulin. Current immunotherapy strategy is inhibiting or deleting the lymphocyte subset and/or through the use of agents which will induce the tolerance by activating regulatory T cell such as the use of anti-CD3. Therapy using monoclonal antibody also has a continous effect as compared to immunosupressive agents that traditionally being used.Methods: A systematic review was conducted based on PRISMA through PubMed, ScienceDirect, Directory of Open Access Journal, Wiley, Cochrane Library, Google Scholar, and Scopus, searching for randomized controlled trials which analyze anti-CD3’s effects on clinical outcomes of T1DM patients. Studies selected were then assessed for bias risk with CONSORT criteria. Random-effects meta-analysis was performed to estimate the pooled mean difference (MD) along with their 95% confidence intervals (CIs).Results: The search yielded ten RCTs with a total of 1,458 subjects. Anti-CD3 intervention is proven to be effective in reducing insulin’s usage (MD -0,18 [95% CI: -0.22, -0.13],I2=59%, p<0,0001) and HbA1C (MD -0.71[95% CI: -1.18, -0.24], I2=78%, p=0.003) significantly. Furthermore, there is another clinical benefits, such as reducing the decrease of C-peptide response significantly. Conclusion: To conclude, anti CD-3 showed promising results to be widely implemented as treatment for T1DM patients.